Scots roses in Northern Ukraine - Olena Rubtsova; Оlena Kolesnichenko; Mykola Shumyk; Oleksandr Shynder; Valentyna Chyzhankova; Anzhela Dzyba; Sergey Hrysiuk (Horticultural Science, 2021)
The article presents the results of the evaluation of eleven Scots rose cultivars in the northern part of Ukraine due to its severe winter conditions. A range of variations regarding the bloom colour, bloom size, bloom type, flowering incidence, plant size was noticed. The evaluation showed the decorative value and considerable frost resistance of the varieties 'Double White', 'Dunwich Rose', 'Frühlingsduft', 'Frühlingsgold', 'Frühlingsmorgen', 'Karl Forster', 'Mon Amie Claire', 'Red Nelly', 'Stanwell Perpetual', 'Suzanne', and 'William III'. The varieties studied can be used for decorative purposes in urban landscapes in the northern part of Ukraine.